Gas-chromatographic measurements of atmospheric CF2Cl2, CFCl3 and N2O in Antarctica - Hirota, Michio; Chubachi, Shigeru; Makino, Yukio; Muramatsu, Hisafumi (1984)
P(論文) Atmospheric CF_2Cl_2,CFCl_3 and N_2O were measured by a gaschromatographic method. Air samples were obtained by the 23rd and 24th Japanese Antarctic Research Expeditions. Vertical distributions of these gases over Syowa Station were observed on January 24,1983,and they showed very uniform distributions up to an altitude of 6.4km. Mean volume mixing ratios and their standard deviations for five samples were (32)_1 and _3 ppt for CF_2Cl_2,(18)_2 and _6 ppt for CFCl_3,and (29)_8 and _2 ppb for N_2O, respectively. Mean values of CF_2Cl_2 and CFCl_3 and (29)_8 and _2 ppb for N_2O, respectively. Mean values of CF_2Cl_2 and CFCl_3 were lower than those observed over Japan from October 1982 to February 1983 by (4±3)% and (6±7)% respectively. A similar result was also obtained in the latitudinal distribution of CF_2Cl_2 from Japan to Syowa Station (November 1982-January 1983). CF_2Cl_2 and CFCl_3 at Syowa Station showed rather large rates of increase during 1982 (2_8 and 1_8 ppt/year). In the same period, N_2O was quite constant (((29)_8±_3)ppb) at Syowa Station. departmental bulletin paper